Hubungan intensitas penggunaan Artificial Intelligence (AI) dengan Kemampuan berpikir kritis mahasiswa PAI - Hafidhoh Hidayati; Ainol Ainol; Arifia Retnayunita (Al-Liqo: Jurnal Pendidikan Islam, 2026)
This study aims to analyze the relationship between the intensity of Artificial Intelligence (AI) usage and students' critical thinking patterns. While previous research has extensively discussed the general effectiveness of AI in learning, studies specifically linking AI usage intensity with critical thinking skills in the context of Islamic Religious Education (PAI) students remain limited. The novelty of this research lies in its attempt to position AI as an academic instrument with ambiguous impacts between task efficiency and the depth of independent analysis. Using a quantitative correlational design, this study involved 105 eighth-semester students of the PAI Study Program at Zainul Hasan Genggong Islamic University. Data were collected via questionnaires and analyzed using simple linear regression tests. The results showed a correlation coefficient (r) of 0.191. These findings indicate a statistically significant positive relationship, yet it falls into the very weak category. This suggests that AI usage provides only a very limited contribution to critical thinking, which is more predominantly influenced by external factors such as academic culture and classroom discussions. Consequently, AI serves as an information access tool rather than a primary determinant in the formation of students' critical thinking abilities.